Speaking effective English! - Zoller, Bettye Pierce; Watkins, John Arthur; Lampman, Hugh (New York : ZWL Publishing, 1996)
Three of America's top voice coaches give you the tools you need to speak clearly, powerfully, and effectively--and get what you want through the power of speech! Learn how to make a knockout first impression, how to minimize accents and dialects, how to overcome stage fright, and much more.
Title from container
Keywords: Speech; Public speaking; Oral communication